Zunanje ocenjevanje šolskega eseja na splošni maturi od začetka do danes - Šimenc, Brane (Jezik in slovstvo, 2015)
The present contribution deals with the external evaluation of Examination Paper No. 1, i.e., the school essay, from the practical and operational point of view. It first presents the current practices of evaluation and the achieved results, then addresses the evaluation of the tasks at the time of the introduction of the matura exam, and finally describes the development of the evaluation to the present day, as dictated by the experience gained, the changes in the syllabus, and the increased competence of the candidates in solving textually demanding tasks. The development of the first matura exam paper and its evaluation is divided into two periods, with the year 2002 as the dividing line.
Keywords: šolski esej; razpravljalni esej; interpretativni esej; navodila za ocenjevanje; ocenjevalni obrazci; zunanje ocenjevanje; splošna matura; Slovene; slovenščina